Revamping hospitals’ online communication strategies: A humanistic approach to build meaningful brands - Medina Aguerrebere, Pablo; Medina, Eva; Gonzalez Pacanowski, Toni (Revista Española de Comunicación en Salud, 2024)
Introduction: Hospitals implement artificial intelligence, big data, and telehealth to accelerate digital transformation and improve quality standards. However, their corporate communication strategies remain very conservative (brochures, magazines, websites) and inconsistent with their ambitious organizational goals. Objective: This literature review-based paper analyzes how hospitals should use technology to revamp their online communication strategies and build more meaningful brands. Methodology: To do that, we conducted a literature review on digital hospitals, their branding strategies, and their stakeholders’ humanistic needs. Based on that, we proposed an online communication model to help hospitals build credible brands. Conclusion: We concluded that these organizations should focus their communication efforts on sharing credible content that describes how their medical initiatives improve society; they should assist their stakeholders in enhancing their global understanding of healthcare; and they should help the Digital Communication Unit lead an intellectual reflection about how to develop a smart hospital from a technology and humanistic perspective.